1990
DOI: 10.1093/jn/120.7.760
|View full text |Cite
|
Sign up to set email alerts
|

Iron Retention by Rats from Casein-Legume Test Meals: Effect of Tannin Level and Previous Diet

Abstract: The effect of tannin content on iron (Fe) bioavailability from several legumes was evaluated. Absorption of Fe from a casein (C), isolated soy protein (ISP), chickpea (CP) or red kidney bean (RKB) test meal was tested in marginally Fe-deficient rats [9.9 +/- 0.2 g Hb/100 mL (mean +/- SD)] using the extrinsic tag technique. Also, the effects of a casein habitual diet or of one of three casein-legume habitual diets fed before and after the test meal were investigated. Weanling male rats were fed the habitual die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…The algorithm predictions (20) were also inaccurate unless the polyphenol or tannin adjustment was eliminated. Although previous in vitro analyses (18,33,34) suggested that polyphenolic compounds, which contribute pigment to colored beans, bind iron and render it unavailable for absorption, this has not been confirmed in animals (35,36), nor was it confirmed in the present human study. Bean pigmentation is commonly attributed to flavonoid, not tannin, polyphenols.…”
Section: Discussioncontrasting
confidence: 85%
“…The algorithm predictions (20) were also inaccurate unless the polyphenol or tannin adjustment was eliminated. Although previous in vitro analyses (18,33,34) suggested that polyphenolic compounds, which contribute pigment to colored beans, bind iron and render it unavailable for absorption, this has not been confirmed in animals (35,36), nor was it confirmed in the present human study. Bean pigmentation is commonly attributed to flavonoid, not tannin, polyphenols.…”
Section: Discussioncontrasting
confidence: 85%
“…A study in weanling rats looked at differences in iron availability with condensed tannin in habituated compared with naïve rats. There were no significant differences between habituated and naïve rats' iron status at study end ( 51 ). A 4-wk hemoglobin depletion-repletion study in piglets that consumed meals with significantly different tannin amounts from red or white bean feed found no differences in hemoglobin, hemoglobin repletion-efficiency (hemoglobin replaced per iron intake), or weight gain at endpoint ( 36 ).…”
Section: Resultsmentioning
confidence: 88%
“…Although only the acute effect of PP was studied in the present study, PP were fed for 3 d before administrating 65 Cu-and 67 Zn-labelled test meals to rats, to avoid the effect of previous meals. Indeed, it is known that diets fed before test meals can affect postprandial mineral absorption (Garcia-Lopez et al 1990).…”
Section: Without Correctionmentioning
confidence: 99%